Frequency of Sexual Problems and Related Psychosocial Characteristics in Cancer Patients—Findings From an Epidemiological Multicenter Study in Germany - Heyne, Svenja; Esser, Peter; Geue, Kristina; Friedrich, Michael; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2021)
Background: Multimodal cancer treatments are often associated with sexual problems. Identifying patients with sexual problems could help further elucidate serious issues with their sexuality and thus promote or maintain patients' sexual health. We aimed to assess the occurrence of sexual problems in patients across different tumor locations and to explore associated sociodemographic, medical and psychosocial factors. Methods: We included 3677 cancer patients (mean age 58 years, age range 18-75 years, 51.4% women) from a large epidemiological multicenter study in Germany on average 13.5 months after cancer diagnosis. The occurrence and frequency of sexual problems were assessed via a binary item on the problem checklist of the Distress Thermometer (DT). Controlled associations of these problems with sociodemographic, medical and psychosocial factors including distress (DT), anxiety (GAD-7), depression (PHQ-9), quality of life (EORTC-QLQ-C30) and social support (SSUK-8) are analyzed using logistic regression analysis. Results: We found that 31.8% of patients reported sexual problems, with a significant higher proportion in men (40.5%) compared to women (23.7%), OR 2.35, 95% CI [1.80-3.07] and a higher proportion in patients with a partner (35.6%) compared to those without a partner (3.5%), OR 2.83, 95% CI [2.17-3.70]. Tumor location was associated with occurrence of sexual problems: patients with cancer, affecting the male genital organs had the highest chance for sexual problems, OR 2.65, 95% CI [1.18-3.95]. There was no significant difference in the occurrence of sexual problems between age groups OR 0.99, 95% CI [2.13-3.53] and type of therapy (e.g., operation OR 0.91, 95% CI [0.72-1.15]). Sexual problems were further associated with elevated levels of anxiety, OR 1.05, 95% CI [1.02-1.10], less social support, OR 0.93, 95% CI [0.90-0.97] and lower quality of life in terms of impaired functioning (e.g., social function, OR 0.99, 95% CI [0.99-1.00]). Conclusions: Sexual problems are commonly reported by patients. Male patients and those living with a partner are more likely to report sexual problems. Sexual problems are associated with different aspects of well-being. The findings imply the practical relevance to screen for sexual problems among patients and identified groups that should be particularly monitored.